Using ICT tools to increase farmers’ resilience to climatic risks - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
CCAFS South Asia is working with national partners and CGIAR centres in the region to study the potential to deliver timely and accurate agromet advisories and provide climate information to farmers through mobile phones and radio. We have tested projects in partnership with IFFCO Kissan Sanchar Limited in India and the Nepal Development Research Institute (NDRI), using mobile phones, radio and the internet.